Myth-Busting? Confronting Six Common Perceptions about Unconditional Cash Transfers as a Poverty Reduction Strategy in Africa - Handa, Sudhanshu; Daidone, Silvio; Peterman, Amber; Davis, Benjamin; Pereira, Audrey; Palermo, Tia; Yablonski, Jennifer (Published by Oxford University Press on behalf of the World Bank, 2020)
This paper summarizes evidence on six perceptions associated with cash transfer programming, using eight rigorous evaluations conducted on large-scale government unconditional cash transfers in sub-Saharan Africa under the Transfer Project. Specifically, it investigates if transfers: 1) induce higher spending on alcohol or tobacco; 2) are fully consumed (rather than invested); 3) create dependency (reduce participation in productive activities); 4) increase fertility; 5) lead to negative community-level economic impacts (including price distortion and inflation); and 6) are fiscally unsustainable. The paper presents evidence refuting each claim, leading to the conclusion that these perceptions—insofar as they are utilized in policy debates—undercut potential improvements in well-being and livelihood strengthening among the poor, which these programs can bring about in sub-Saharan Africa, and globally. It concludes by underscoring outstanding research gaps and policy implications for the continued expansion of unconditional cash transfers in the region and beyond.